2020
DOI: 10.1002/pat.4989
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the flexoelectric‐like response of poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) thin films

Abstract: In the last decade, the polymeric poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) semiconductor has been widely studied for their electrical and electrochemical properties and used in various applications such as flexible and transparent electrodes, optoelectronics and thermoelectric devices. Here, we report the intrinsic electromechanical coupling in trilayered stainless steel/PEDOT:PSS/Aluminum composites. The PEDOT:PSS thin film integrated in the multi‐layer serves as the transduction ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In previous work, 31 it was experimentally observed that PEDOT:PSS films deposited onto stainless steel substrate, with conductivity greater than 10 −2 S/m do not exhibit a flexoelectric-like effect. The same behavior is observed with the Relative permittivity, dielectric loss factor, and dynamic conductivity measurements for PEDOT:PSS solutions (1:6 ratio) on different substrates were also performed (see the section entitled "Dielectric Characterization of PEDOT:PSS on Different Substrates" in the Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In previous work, 31 it was experimentally observed that PEDOT:PSS films deposited onto stainless steel substrate, with conductivity greater than 10 −2 S/m do not exhibit a flexoelectric-like effect. The same behavior is observed with the Relative permittivity, dielectric loss factor, and dynamic conductivity measurements for PEDOT:PSS solutions (1:6 ratio) on different substrates were also performed (see the section entitled "Dielectric Characterization of PEDOT:PSS on Different Substrates" in the Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
“…In previous work, it was experimentally observed that PEDOT:PSS films deposited onto stainless steel substrate, with conductivity greater than 10 –2 S/m do not exhibit a flexoelectric-like effect. The same behavior is observed with the freestanding PEDOT:PSS (1:2.5) films in this study, which tends to show that PEDOT:PSS (1:2.5) is not suitable for flexoelectricity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Conductive polymers contain conjugated structures in backbone, which provide electrical conductivity due to the π bonds overlapping and creating of large chain segments where π-electrons are delocalized. Popular conjugated polymers, such as polyaniline, polypyrrole and polythiophene are extensively used in various applications since they show satisfying processability and high electrical conductivity [15,16,17]. Among others, polythiophene derivative, poly(3,4-ethylenedioxythiophene) (PEDOT), in a complex with poly(styrenesulfonate) (PSS) exhibits many valuable properties, in particular, water solubility, electrochemical and thermal stability, and relatively large conductivityup to 900 S cm À1 [18].…”
Section: Introductionmentioning
confidence: 99%